Vitamin B12 dan Anemia Megaloblastik - Harjani, Harjani (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1981)
Vitamin B12 is an essential factor for DNA synthesis, and it is also needed in the reaction for the production of lipoprotein in myelin sheaths of the nerve system.It is known that vitamin B12 deficiency causes.among others disturbances in the nucleus formation and leads to megaloblastic anemias, with or without disturbances of the peripheral nerve system. Disturbances in the nucleus formation affect cells of tissues which have a relatively rapid turnover such as hemopoiedc precursors in the bone marrow and the mucosal epithelium of the gastrointestinal tract.As the importance of the role of the vitamin in the formation and the development of cells and as the deficiency of the vitamin may initiate a vicious circle which aggravates more and more the deficiency and the defect of the gastrointestinal mucosa, it is very important to cut the circle with, for example, a high dose of parentera I vitamin B12 with sufficient quantity and quality of food.Key Words: gastric intrinsic factor - methylcobalamin - hydroxocobalamin megaloblastic - anemia - vitamin B12